Pelatihan Budaya Sasak Lombok pada Pembuatan Kue Tradisional Sumping di SMP Diyaul Azahar Lombok Timur - Lalu Amrullah; Affan Gaffar; Ziana Warsani; Soufa Malita; Yuliatin Hasfiani; Rahayu Safitri Rahman; Nurramdaniyah Nurramdaniyah; Vivi Andrianingsih; Muhamad Taqiudin (Universitas Veteran Bangun Nusantara Sukoharjo, 2024)
Diyaul Azahar Middle School, East Lombok, Bagik Umbrella Village has the potential for local food in the form of cassava which is generally processed simply for personal consumption or sold as a home business. This simple processing causes the value and selling price of the product to be low. This community service activity aims to improve the ability of students from Benda Baru sub-district in processing cassava and innovate in making traditional cakes which can increase the selling value of processed cassava products as an effort to improve family welfare. This activity was attended by 19 participants who were housewives in Benda Baru sub-district which was carried out using lecture, demonstration and evaluation methods.